2011
DOI: 10.2136/sssaj2010.0275
|View full text |Cite
|
Sign up to set email alerts
|

Black Spruce Soils Accumulate More Uncomplexed Organic Matter than Aspen Soils

Abstract: Improving knowledge on the dynamics and maintenance of the boreal soil's C pool is ot particular importance in response to climate change concerns. We hypothesized that different forest types (black spruce, trembling aspen, and mixedwood) found on a similar site type differentially affect soil organic carbon (SOC) distribution among physical fractions. The surface mineral soil (0-15 cm) of 24 plots differing in forest composition was sampled in forested Hapludalfe of the Abitibi-James Bay region, Canada. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 47 publications
1
21
1
Order By: Relevance
“…The relative distribution of SOC among the different fractions (expressed by the percent of SOC) was similar across the vegetation types in plots and transects, probably due to the high variability in LF content in our sites. These results somewhat contradict previous observations from montane semi-arid [26] and boreal aspen-conifer forests [30], where aspen stands had a significantly higher proportion of SOC in the MoM fraction than mixed and conifer stands. Table 4.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…The relative distribution of SOC among the different fractions (expressed by the percent of SOC) was similar across the vegetation types in plots and transects, probably due to the high variability in LF content in our sites. These results somewhat contradict previous observations from montane semi-arid [26] and boreal aspen-conifer forests [30], where aspen stands had a significantly higher proportion of SOC in the MoM fraction than mixed and conifer stands. Table 4.…”
Section: Resultscontrasting
confidence: 99%
“…), while mineral-associated SOC content was similar across the pine-oak ecotone. Similarly, Laganiè re et al [30] did not find differences in mineral-associated SOC between aspen and black spruce (Picea mariana (Mill.) Britton et al), but reported more SOC in less protected fractions under black spruce.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Some data on differences in mechanisms associated with soil organic matter (SOM) stabilization in forest soils were provided by Laganière et al (2011). There are few data available for mountain soils, and our understanding of the effect of various environmental factors on SOM turnover is limited Budge et al, 2011;Martinsen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%